The missing shifts - SINDHWANI, Saumya (Institutional Knowledge at Singapore Management University, 2019)
Saumya Sindhwani, Jerry Connor and Howard Thomas argue it is time to change the way we develop leaders – and tap into the power of mindset. The needs the managers speak of fit into two broad categories (“empathy” and “resourcefulness”) and both are fundamental “changes in mindset”. By that, we mean a change in attitude or world view.